Resection of puncture site necrosis over an arteriovenous fistula: Endoclamp use for preservation of cannulation sites. Issue 3 (May 2018) - Mallios, Alexandros; Jennings, William; Boura, Benoit; Costanzo, Alessandro; Combes, Myriam
Skin necrosis overlying an arteriovenous fistula at the cannulation site is a common and potentially life-threatening problem, often associated with underlying aneurysm formation. Arteriovenous fistula-skin necrosis generally requires resection of surrounding skin margins and the underlying aneurysmal vessel wall, allowing repair with healthy tissue of the arteriovenous fistula in addition to closure of soft tissue and skin. In patients with insufficient fistula length, salvage of these arteriovenous fistulas may result in difficult or insurmountable cannulation issues leading to attempts at one-needle cannulation dialysis or, most often, catheter placement. Pre-existing stents or extensive calcification may add to the technical challenge of gaining proximal and/or distal control. We describe our technique for dealing with such arteriovenous fistula-skin necrosis lesions utilizing endo-occlusion with an angioplasty balloon for vascular control, allowing a limited incision and tissue resection with preservation of arteriovenous fistula cannulation length.